A Current Portrait of Islamic Education in Aceh - Kamaruzzaman Bustamam Ahmad (UIN Sunan Gunung Djati Bandung, 2014)
There have been many studies on Islamic education in Aceh, especially among traditional institutions. However, the new coming of ustaz Java has led to social dynamic in the province. This paper aims to examine the contemporary of Islamic authority in education in Aceh, Indonesia. It will focus with two social concepts and their role in society. It based from fieldwork in Aceh in several areas. It is argued that there is changing of Islamic authority the society in which the ustaz play more important role in education rather than teungkue. Meanwhile, the teungku are more interested in political arena.